PENYALIBAN YESUS DALAM PERSPEKTIF PSIKOLOGIS UMAT KRISTEN DAN UMAT ISLAM - Dian Nur Anna (Religi: Jurnal Studi Agama-agama, 2016)
This article aims to understanding the crucifixion of Jesus according to bothChristians and Muslims in psychological perspective. This article try to illustrate how Christians and Muslims talk about the crucifixion of Jesus and the possibility to make an understandable between both religions. Christianity be-lieves that Jesus was dead on the cross for salvation. Islam, as a religion begin-ning after Christianity, also respects Jesus, especially the death of Jesus. Muslims have different opinions about the death of Jesus which divided them into two groups. The first group believes that Jesus did not crucify and did not die on the cross. The second groups of Muslims agree that Jesus crucified, but maintain that he did not die on the cross. Based on this article, it can know the meaning of crucifixion of Jesus from both Christians and Muslims in psychological perspective. For Christians, the mean-ing of crucifixion of Jesus is a proof of love and triumph of God. Jesus is an incarnation of God dead to redeem a great sin of human being and he was resurrected. For Muslims, the meaning of crucifixion of Jesus is a proof of love and triumph of God. God save Jesus from death on the cross with take Jesus beside God. Then, Muslims can understand how God sent Jesus as human to redeem human beings and God loves Jesus as a prophet with special status.